Collaboration Across Boundaries for Social-Ecological Systems Science Experiences Around the World - Perz, Stephen G. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
XLV, 437 p. 40 illus., 33 illus. in color.